Survival of immature pre-adult Gnathostoma spinigerum in humans after treatment with albendazole - Kanjanapruthipong T. (2023)
Human gnathostomiasis is a food-borne zoonotic helminthic infection widely reported in Latin America, Asia and Southeast Asia, particularly in Thailand. There are increasing reports of the parasite in countries where it is not endemic. A study of the survival drug-treated immature stage (STIM) of Gnathostoma spinigerum recovered from infected patients focused on their integument surface using scanning electron microscopy (SEM). STIM displayed a specific, characteristic head bulb, with a pair of large thick equal-sized trilobulated lips in the centre. Cephalic spines had eight transverse rows on the head bulb with single-ended tips curved posteriorly. Body cuticular spines on the anterior half of the STIM were not sharp-pointed but distributed more densely, with multi-dentated-cuticular spines, irregularly arranged in a lining pattern of velvety cuticular folds. The length of cuticular spines increased caudally. The size of spines became gradually smaller, and numbers decreased towards the posterior end. Spines were still widely dispersed posteriorly as their density dropped. The morphology of STIM of G. spinigerum are described in detail for the first time. These specimens showed structural adaptation based on changes on integument surfaces, probably to protect against damage induced by the toxic effects of albendazole.